Sistem Pendukung Keputusan Penerimaan Karyawan Menggunakan Metode Weighted Product (WP) Pada BMT NU Cabang Suboh - Moh. Riqza Al Halimi; Muhammad Ali Ridla; Adi Susanto (Universitas Islam Raden Rahmat, Malang, 2024)
Employees are one of the company's most valuable assets. Employees are very important human resources for the company. To obtain employees who suit the office's needs, recruitment is carried out. KSPP Syariah BMT NU is a Sharia-based Savings and Loans Cooperative financial institution. The selection process for new employees is still carried out manually using an administrative system so it takes quite a long time to determine who will be accepted. This research uses the Weighted Product (WP) method with the aim of assisting in the employee recruitment process. In the employee recruitment process six criteria are used, namely Completeness of Application Files, Recent Education, Work Experience, Age, Ability Test and Interview Test. The results of this research determined that the highest score with first rank was Alternative 6 with a score of 0.1628. The aim of this research is to make it easier and faster to select employees who best meet office needs.